2020
DOI: 10.1155/2020/9614574
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of Pathological Patterns in a Young Population with Dysfunctional Breathing

Abstract: Dysfunctional breathing (DB) is characterized by abnormal breathing patterns and often results from psychogenic causes in the absence of organic diseases. Although acupuncture and herbal treatments have been suggested as alternative therapies for DB, few studies have addressed the relationship between DB and pathological patterns from a diagnostic perspective. We asked 237 college students (130 men aged 21.4 ± 1.9 years; 107 women aged 21.4 ± 3.0 years) to complete the Korean version of the General Health Ques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Rather, the "fatigue" factor scores of YDS had "strong" positive correlations with the scores of "neuropsychological," and "neurogastrointestinal" factors. Tis result may not guarantee the causality of YD-related fatigue with neuropsychological or neuro-gastrointestinal symptoms [13,20]. Correlations between the factor scores of the factor-based YDS and the KNQ suggest that fatigue due to YD needs to be monitored and treated more intensively than other etiological or symptomatic factors of YD in patients with dysfunctional breathing.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Rather, the "fatigue" factor scores of YDS had "strong" positive correlations with the scores of "neuropsychological," and "neurogastrointestinal" factors. Tis result may not guarantee the causality of YD-related fatigue with neuropsychological or neuro-gastrointestinal symptoms [13,20]. Correlations between the factor scores of the factor-based YDS and the KNQ suggest that fatigue due to YD needs to be monitored and treated more intensively than other etiological or symptomatic factors of YD in patients with dysfunctional breathing.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding vocal quality, increased YDS scores were associated with decreased modulation of the fundamental frequency [12]. Te YDS scores for the young population with dysfunctional breathing (DB) were higher than those without DB [13]. Although the YDS has been broadly utilized to estimate the clinical severity of YD, it has 27 items, which may require response time and the ability to complete it [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the vocal quality of normal subjects, especially decreased tremor-related parameters and increased resonance-related parameters, was found to be associated with increased PPQ scores [ 11 ]. Recently, a study reported higher PPQ scores in a dysfunctional breathing group than in a nondysfunctional breathing group, suggesting that the clinical severity of phlegm may be associated with the aggravation of dysfunctional breathing [ 12 ].…”
Section: Introductionmentioning
confidence: 99%